A study on green building element adaptation at green certified shopping mall / Muhammad Nureman Kamar Jaman and Nur Fadhilah Bahardin - Kamar Jaman, Muhammad Nureman; Bahardin, Nur Fadhilah (2023)
This research study investigates the implementation of green building elements in existing shopping malls to promote sustainability and reduce environmental impacts in the retail sector. By analyzing green certified shopping malls, the study identifies key elements and provides recommendations to overcome implementation challenges, contributing to sustainable building practices. The research methodology employs a quantitative approach, using online questionnaires as the primary data collection method, supplemented by secondary data from literature reviews. The findings reveal that green building elements such as proximity to public transport, natural lighting, and smart building systems are commonly adopted Ultimately, this study offers practical solutions to guide the construction and retail industries towards more sustainable building practices, thereby supporting a greener future.